ANALISIS STILISTIKA DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL KOMET KARYA TERE LIYE - Hermawan, Novi (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2019)
This study aims to describe and explain diction, figurative language, sentence style, discourse style, images, and the educational value of the Comet novel character by Tere Liye. This research is a descriptive qualitative research. Research sites are site bound. The data in this study is the Comet novel by Tere Liye. Data analysis in this study used the technique of reading and note taking. The results of this study can be concluded into six conclusions. First, the dominant Comet novel by Tere Liye includes: connotative words, concrete words, absorption words, and foreign words. Second, the dominant figurative language of the Comet novel by Tere Liye, namely: metaphor, simile, and hyperbole. Third, the dominant sentence style of the Comet novel by Tere Liye, namely: repetition sentence style. Fourth, the dominant comet style of Tere Liye's Comet novel, namely: repetition discourse style, and code switching discourse style. Fifth, the dominant Comet novels by Tere Liye include visual images, auditory images, tactile images, and olfactory images. Sixth, the dominant value of the character education of the novel Comet by Tere Liye namely: love of the motherland, and social care. Keywords: stylistic, Comet, the value of character education.